2016
DOI: 10.4103/1735-1995.177355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori eradication on insulin resistance among prediabetic patients: A pilot study and single-blind randomized controlled clinical trial

Abstract: Background:Type II diabetes mellitus (T2DM) is the prevalent type of diabetes in the world. Prediabetic patients are the most probable group to get diabetes. Several studies have mentioned the role of inflammation in the incidence of diabetes. The origin of inflammation can be infection such as Helicobacter pylori (HP) infection. This study was designed to explore the effect of HP eradication on insulin resistance.Materials and Methods:This single-blind randomized controlled clinical trial was conducted in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Wada et al also found that successful eradication of H. pylori could not improve glucose control of DM in Japanese patients [ 55 ]. Furthermore, a recent randomized controlled trial involving 49 H. pylori -infected subjects in a prediabetes stage showed that H. pylori eradication resulted in an increased Homeostatic model assessment of insulin resistance (HOMA-IR) [ 56 ].…”
Section: Metabolic Syndrome and Diabetes Mellitus (Dm)mentioning
confidence: 99%
“…Wada et al also found that successful eradication of H. pylori could not improve glucose control of DM in Japanese patients [ 55 ]. Furthermore, a recent randomized controlled trial involving 49 H. pylori -infected subjects in a prediabetes stage showed that H. pylori eradication resulted in an increased Homeostatic model assessment of insulin resistance (HOMA-IR) [ 56 ].…”
Section: Metabolic Syndrome and Diabetes Mellitus (Dm)mentioning
confidence: 99%
“…Chronic rise in blood glucose levels is termed as the hyperglycemia. [ 1 2 ] Chronic hyperglycemia associated with oxidative stress in DM produces a variety of glucose-derived toxic agents called the “α-oxoaldehydes.” The α-oxoaldehydes react with N-terminal amino group of proteins to form the advanced glycation end products (AGEs). [ 3 ] Methylglyoxal (MGO) is one of the α-oxoaldehydes which interferes with cell functions, insulin signaling, and β-cell functions.…”
Section: Introductionmentioning
confidence: 99%
“…All trial authors designed control agents that had a similar taste and texture to glycerol for concealment purposes, and whether any of the substances used exerted an independent osmotic action is untested. However, the higher mortality reported by Ajdukiewicz 2011 in the glycerol group suggests that glycerol had an action beyond any osmotic effect exerted by the dextrose placebo, particularly as the glycerol was diluted in dextrose for some participants (Brouwer 2011). …”
Section: Discussionmentioning
confidence: 99%
“…We were unable to control for this effect in the analysis, which may have introduced further heterogeneity (Brouwer 2011; Saez-Llorens 2007). Prolonged use of osmotic agents, such as the four-day courses of glycerol used in Ajdukiewicz 2011, have been suggested to be harmful.…”
Section: Discussionmentioning
confidence: 99%